Interactions between astrocytes and extracellular matrix structures contribute to neuroinflammation-associated epilepsy pathology - Woo, AnnaLin M.; Sontheimer, Harald (Frontiers in Molecular Medicine, 2023)
Often considered the "housekeeping" cells of the brain, astrocytes have of late been rising to the forefront of neurodegenerative disorder research. Identified as crucial components of a healthy brain, it is undeniable that when astrocytes are dysfunctional, the entire brain is thrown into disarray. We offer epilepsy as a well-studied neurological disorder in which there is clear evidence of astrocyte contribution to diseases as evidenced across several different disease models, including mouse models of hippocampal sclerosis, trauma associated epilepsy, glioma-associated epilepsy, and beta-1 integrin knockout astrogliosis. In this review we suggest that astrocyte-driven neuroinflammation, which plays a large role in the pathology of epilepsy, is at least partially modulated by interactions with perineuronal nets (PNNs), highly structured formations of the extracellular matrix (ECM). These matrix structures affect synaptic placement, but also intrinsic neuronal properties such as membrane capacitance, as well as ion buffering in their immediate milieu all of which alters neuronal excitability. We propose that the interactions between PNNs and astrocytes contribute to the disease progression of epilepsy vis a vis neuroinflammation. Further investigation and alteration of these interactions to reduce the resultant neuroinflammation may serve as a potential therapeutic target that provides an alternative to the standard anti-seizure medications from which patients are so frequently unable to benefit.